Geographical Analysis of Increasing Urban Population in Koya District from (1957-2020) (Raparin Journal of Humanities (RJH), 2022)
The population of the world has been increasing year by year and it is growing rapidly in the cities and towns too، especially in the third world.There are some factors for that phenomenon, It is regarded as a new feature of modern civilization. This has an impact on the cities and towns both negatively and positively. The research zone like one town is subject to this phenomenon can be geld easily from its building up to now. In away, the study zone is broken down in to six administrative units which are (The central sub-district, Taq Taq, sub-district, shorsh, sub-district, Ashty, sub-district, sub-district, Siktan, sub-district, and Segirtkan, sub-district) the number its population reacher (148852)and the ratio of urban growth reachs (%5.1)and its area is (2069)km .It seems that this growth increases in the future and leaves its concequences .The current study consists three secfions:the first section introduces the region and concept .It the second section, the growth of the population in the research zone has been explained generally .In the third seotion, urbanization feature whiche are (natural factor and humanity) has been taekled.